An integrated approach to analyse requisites of product innovation management. (2018) - Kumar, Sanjay; Luthra, Sunil; Haleem, Abid; Garg, Dixit; Singh, Sultan; Mangla, Sachin K.
Product innovativeness, in terms of significantly improved/new features, functions, usage, properties and aesthetics, etc., may be appreciated as an increasingly important research area for attaining business sustainability nationally/internationally. This paper attempts to identify, understand and analyse key requisites for product innovation management in Indian firms. Literature review approach has been utilised for identifying requisites and benefits of product innovation management. Interpretive structural modelling is utilised to understand and analyse contextual relations and hierarchical levels of requisites of product innovation management. Further, through decision making trial and evaluation laboratory methodology used to segregate requisites for product innovation management in to cause and effect groups. This paper may also help practicing innovation managers of various Indian firms and multinational firms seeking business in/from India towards identifying, developing an understanding and analysing 'strengths and weaknesses' of their firms in managing activities and resources involved in 'product innovation management processes'.